YONG, Amos. Renewing the Church by the Spirit: Theological Education after Pentecost. - Cartledge, Mark J. (PentecoStudies, 2021)
YONG, Amos. Renewing the Church by the Spirit: Theological Education after Pentecost. Grand Rapids, MI: Eerdmans, 2020. 151pp. Pbk. ISBN: 978-0-8028- 7840-3. £15.00.